Aesthetic Parameters and Patient-Perspective Assessment Tools for Maxillary Anterior Single Implants - Kelvin I. Afrashtehfar; Mansour K. A. Assery; S. Ross Bryant (International Journal of Dentistry)
Background. This review aimed to concisely describe the current aesthetic objective indices for a single-implant maxillary anterior crown. The secondary aim was to propose introducing a unified, standardized questionnaire for adequately collecting patient-reported outcome measures (PROMs) in implant dentistry. Materials and Methods. A literature review was conducted using both EMBASE/Ovid and MEDLINE/PubMed databases by combining keywords and Emtree/Mesh terms related to “Esthetics,” “Self-Assessment or Surveys and Questionnaires,” and “Single-Tooth Dental Implants.” Results. The most meaningful aesthetic objective indices for single implants in the literature are the Pink Esthetic Score (PES), the Papilla Presence Index (PPI), Peri‐Implant and Crown Index (PICI), PES/White Esthetic Score (PES/WES), the Implant Crown Aesthetic Index (ICAI), and a modified version of the ICAI (mod-ICAI) index. Clearly, PES/WES is still the most widely accepted tool. It is encouraging to observe that there is an increasing tendency in recent years to report PROMs more frequently in the implant dentistry literature. We proposed the implementation of a unified, standardized questionnaire using a self-administered visual analogue scale (VAS) scoring system, which evaluates overall satisfaction, comfort, tooth appearance, gingival appearance, function, and hygiene complexity. This tool should be validated in the oral implantology research context for its regular implementation or further development. Conclusions. Conducting qualitative studies among dental implant patients who received few implants or single-tooth implant reconstructions in the aesthetic zone may help dental researchers understand better how to efficiently develop and validate a quantitative instrument. This standard tool would reduce heterogeneity bias by providing comparable data between studies.